2021
DOI: 10.1002/jeq2.20205
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between types of cover crop residue and digestate application methods affects ammonia volatilization during maize cropping season

Abstract: Organic and mineral fertilizers are important sources of ammonia (NH3) emissions from agricultural fields. The objectives of this study were (a) to evaluate how different cover crop (CC) residues (i.e., rye [Secale cereale L.], white mustard [Sinapis alba L.], and bare soil as control) in combination with different application methods of digestate (surface broadcast vs. shallow injection) affect NH3 volatilization before planting maize (Zea mays L.) and (b) to assess the residual effect of previous CCs on NH3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Ammonia volatilization results during the experiment have already been reported by Maris, Capra, et al (2021). Here, we use the NH 3 data presented in that article in combination with the N 2 O and NO3 leaching data reported here to compute cumulative N‐losses and yield‐scaled cumulative N losses.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…Ammonia volatilization results during the experiment have already been reported by Maris, Capra, et al (2021). Here, we use the NH 3 data presented in that article in combination with the N 2 O and NO3 leaching data reported here to compute cumulative N‐losses and yield‐scaled cumulative N losses.…”
Section: Methodssupporting
confidence: 81%
“…This was not the case when rye was used as CC, where NH 3 volatilization represented 58% of total yield‐scaled N‐losses. Although rye residues left over the soil surface acted as a mechanical barrier against DLF infiltration into the soil and increased NH 3 volatilization (Maris, Capra, et al, 2021), the strong reductions in NO3‐leaching induced by this CC compensated for this effect, leading to generally lower yield‐scaled N‐losses compared with the other treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original Hutchinson and Mosier (HM) three-points calculation was used when non-linear accumulation was detected; otherwise, Linear Regression has been used (Bertora et al, 2018;Maris et al, 2021). In order to preserve linear conditions, big volume chambers and short deployment times (0-10-20 mins) were used.…”
Section: Ammonia and Greenhouse Gas (Ghg) Emissions Measurementmentioning
confidence: 99%
“…Several studies have shown that fertilization with digestates has higher NH 3 volatilization than does fertilization with raw livestock waste (Möller and Stinner 2009, Ni et al 2012, Crolla et al 2013, Lili et al 2016, Nicholson et al 2017. However, we used relatively low volatilization factors as compared to these references, considering that volatilization could be reduced through phase separation of the digestate (Svehla et al 2020) and/or less-polluting application techniques, such as injection (Riva et al 2016, Maris et al 2021.…”
Section: Discussionmentioning
confidence: 99%